The nitrogen-doped multi-walled carbon nanotubes modified membrane activated peroxymonosulfate for enhanced degradation of organics and membrane fouling mitigation in natural waters treatment. (1st February 2022) - Liu, Yatao; Lin, Quan; Guo, Yuanqing; Zhao, Jing; Luo, Xinsheng; Zhang, Han; Li, Guibai; Liang, Heng
Highlights: The PMS activation by N-MWCNTs and UF membrane filtration were synergistic. The N-MWCNTs-modified membrane/PMS system showed improved catalytic activities. The nonradical processes are dominant in the N-MWCNTs-modified membrane/PMS system. This coupling system effectively mitigated the UF membrane fouling. Abstract: The synthesized catalyst nitrogen-doped multi-walled carbon nanotubes (N-MWCNTs) were introduced into membrane technology for peroxymonosulfate (PMS) activation. The enhanced permeability of the N-MWCNTs-modified membrane might be attributed to the increase in hydrophilicity and membrane porosity. The catalytic degradation and membrane filtration performance for the N-MWCNTs-modified membrane/PMS system in treating different types of natural waters were evaluated. The removal of phenol by the N-MWCNTs-modified membrane was 83.67% in 2 min, which was greater than the phenol removal by the virgin membrane (3.39%) and N-MWCNT powder (41.42%), respectively. Moreover, the resultant membrane coupled with PMS activation exhibited outstanding removal effects on the fluorescent organics in the secondary effluent and Songhua River water. The combination effectively reduced the total membrane fouling caused by the secondary effluent, Songhua River water, and three typical model organics by 28.19–61.98%. Electron paramagnetic resonance and classical quenching tests presented that the active species (SO4 ·−, ·OH, and 1 O2 ) and other non-radical processes generated by N-MWCNTs activated PMS decreased the foulants deposition on the membrane surface. Meanwhile, the membrane interception accelerated the aggregation of pollutants and PMS towards the membrane surface through applied pressure, facilitating their mass transfer to the N-MWCNTs surface for the catalysis exerted more effectively. This study demonstrated the potential application of the coupling of N-MWCNTs catalytic oxidation and the UF, which offers a promising prospect to improve the permeate quality and simultaneously overcome the membrane fouling barriers. Graphical abstract: Image, graphical abstract